Gastrodin protects against high glucose-induced cardiomyocyte toxicity via GSK-3β-mediated nuclear translocation of Nrf2. (September 2021) - Dong, Z; Bian, L; Wang, Y-L; Sun, L-M
Diabetic cardiomyopathy (DCM) is one of the major complications of diabetes that causes mortality and morbidity in diabetic patients. Gastrodin (GSTD) is a bioactive phenolic glucoside component of an ancient Chinese herb Tianma (Gastrodia elata Bl.), which is widely used for cardiovascular and cerebrovascular diseases by ancient Chinese. Up to now, whether GSTD has a beneficial effect on DCM is unclear. Therefore, this study aimed to investigate the effect of GSTD on high glucose-induced injury in H9c2 rat cardiomyocytes and HL-1 mouse cardiomyocytes, and its underlying mechanisms. High glucose (33 mM) treatment caused cardiomyocyte toxicity, oxidative stress and apoptosis in both H9c2 and HL-1 cells. Under both normal (5.5 mM glucose) and high glucose conditions, GSTD showed protective effect against high glucose-induced cytotoxicity and promoted the nuclear translocation of Nrf2 in a concentration and time-dependent manner in H9c2 and HL-1 cells. Knockdown of Nrf2 expression using siRNA specifically targeting Nrf2 attenuated the protective effect of GSTD. Furthermore, GSTD promoted the nuclear translocation of Nrf2 via activating glycogen synthase kinse-3β (GSK-3β) signaling pathway. 4-benzyl, 2-methyl, 1, 2, 4-thiadiazolidine, 3, 5 dione (TDZD-8), an inhibitor of GSK-3β, inhibited the nuclear translocation of Nrf2 induced by GSTD, and attenuated the protective effect of GSTD as Nrf2 knockdown did. In summary, GSTD could protect against high glucose-induced cardiomyocyte toxicity via GSK-3β-mediated nuclear translocation of Nrf2.